Conceptual Study of Tinnitus (Karna Nada)-An Ayurveda View - Sharma, Yogesh Kumar; Fyaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2023)
Background: One of the irritating conditions that can drastically lower a patient’s quality of life and productivity is tinnitus. Even though it is not a life-threatening condition, emotional discomfort, cognitive difficulty, intrusiveness, auditory and perceptual issues, sleep disturbances, and a variety of somatic ailments are the consequences. Its frequency and prevalence are increasing daily. Anticonvulsants, anxiolytics, antidepressants, muscle relaxants, and other pharmacological drugs are now used or being tested for their pacification, but there is little proof that their benefits outweigh their risks. Also poorly understood is the function of neurostimulation therapies, both invasive and non-invasive. Cochlear implantation and the development of hearing aids have not shown, particularly clear results. Materials and Methods: Tinnitus and Karnanada-related information were gathered from texts on Ayurveda, commentaries, and contemporary medicine, respectively. Results: As a result, there is a need to make treatments that are widely recognized, widely successful, and capable of withstanding systematic replication available. These treatments should be able to significantly reduce the volume and impact of tinnitus. Discussion: Tinnitus has numerous etiologies and unexplained causes, which makes it difficult to determine a specific treatment plan today. As a result, the prognosis for the condition is also unknown. However, the prognosis and course of treatment for Karnanada are described in Ayurveda, and we can get better and more satisfied results. Conclusion: Ayurvedic medicine is the most effective treatment for reconstructive ear surgery, and it is best to combine it with herbal remedies.